Generational Accounts, Aggregate Savings, and Intergenerational Distribution - Buiter, Willem (Washington, D.C. : International Monetary Fund, 1996)
Are generational accounts informative about the effect of the budget on the intergenerational distribution of resources and on aggregate saving? First, the usefulness of generational accounts lives or dies with the strict life-cycle model of household consumption. Second, even if the life-cycle model holds, generational accounts ignore the intergenerational redistribution associated with the government's provision of public goods and services and with intergenerational externalities. Third, generational accounting ignores the effect of the budget on tax and transfer bases and on before-tax incomes and prices. That is, it does not handle incidence or general equilibrium repercussions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet